Mites on Caatinga remnants vegetation in Northeast Brazil, with description of a new species of Phytoseiidae (Acari: Mesostigmata) - Rodrigues, J. K. [UNESP]; Almeida-neto, M.; Demite, P. R. [UNESP]; Silva, L. R. A.; Araujo, I. F.; Castro, E. B. [UNESP]; Lofego, A. C. [UNESP] (Systematic & Applied Acarology Soc London, Natural History Museum, 2025)
The Caatinga biome is unique to Brazil, covering approximately 13% of the country's territory with an estimate d area of around 800,000 km2, encompassing 70% of the Northeast Region of Brazil. Studies on the diversity o f mite species in natural areas are still in the early stages yet are essential because understanding the diversity o f these organisms in unexplored environments enables the development of strategies for managing harmful species. Therefore, this study aims to survey Caatinga areas to contribute to the knowledge of the mite diversity occurring in this biome. The study was conducted in three remaining areas of Caatinga, at the followin g collected, representing 32 species from 10 families. The predatory mite family Phytoseiidae was the most diverse, with 14 species recorded. Among the phytophagous mites, three families were particularly represented: Eriophyidae, Tenuipalpidae, and Tetranychidae. However, no phytophagous species were found in hig h abundance. Despite the challenging climatic conditions, the Caatinga biome harbors a considerable diversity o f plant-dwelling mites. In this study, a new species of Phytoseiidae, Amblyseius suassunai sp. nov., is described and illustrated.
Keywords: Biodiversity; Fauna Survey; New Taxon; Phytophagous; Predators; Semi-arid